Reproductive biology of Sphaeralcea species with ornamental interest - Agustina Gutiérrez; Paula Monzón; Sandra Micheletto; Pablo Marinangeli (Advances in Horticultural Science, 2024)
The genus Sphaeralcea belongs to the Malvaceae family and has native species from South America. Their attractive morphological characteristics with ornamental value have not yet been explored. The objective of this work was to know the viability of pollen, stigma receptivity, type of pollination and combining ability of four Sphaeralcea species (S. australis, S. bonariensis, S. crispa and S. mendocina), with the aim to develop new ornamental varieties. Fructification, fertility, seed germination and survival seedlings on intraspecific and reciprocal interspecific offspring were assessed. The highest values ​​of stigma receptivity and pollen viability were obtained at 2:00 pm for the four species. S. mendocina also showed high values ​​of pollen viability at 4:00 pm. The species proved to be self-incompatible and allogamous, with different degrees of reproductive compatibility. The interspecific crosses of S. mendocina and the intraspecific of S. crispa did not produce descendants. The crosses between S. australis and S. bonariensis as maternal parent presented the best combining ability with good fruit production, seed germination and survival. This research provides useful information for the formulation and implementation of breeding strategies, to improve pollination efficiency, and to breed new Sphaeralcea varieties with ornamental potential.